Ionic Liquid‐Assisted Improvements in the Thermal Stability of CH3NH3PbI3 Perovskite Photovoltaics. Issue 8 (10th May 2018) - Du, Jinglun; Wang, Yinglin; Zhang, Yu; Zhao, Guiying; Jia, Yuwen; Zhang, Xintong; Liu, Yichun
Abstract : The instability of perovskite photovoltaic material is the key issue hindering its commercialization. Herein, we report a novel strategy to improve the thermal stability of perovskite materials containing methyl ammonium (MA) by adding a small amount of nonvolatile 1‐butyl‐3‐methylimidazolium bromine (BMIBr) ionic liquid. Nuclear magnetic resonance and scanning electron microscopy measurements show that BMIBr can anchor the MA cation via hydrogen bonding and can reduce the grain boundaries of the perovskite film. BMIBr‐doped perovskite films can tolerate heating for 50 min at 85 °C in contrast to the degradation of the undoped films at the beginning of heating. The retained photovoltaic performance of the perovskite solar cell can also be enhanced from 70 to 85% by BMIBr during thermal degradation at 85 °C for 20 min. This is a novel approach to developing perovskite photovoltaic devices with long‐term stability. Abstract : The thermal stability of CH3 NH3 PbI3 perovskite and its photovoltaic devices can be significantly improved by introducing a small amount of 1‐butyl‐3‐methylimidazolium bromine (BMIBr) ionic liquid to the precursor solution of the perovskite. This performance improvement is mainly attributed to the BMIBr‐assisted grain growth and the hydrogen bond between BMIBr and methyl ammonium group.